Метод двокаскадної імплантації прихованої інформації на основі стеганокомпресійних перетворень 31 - Бараннік, Д.; Barannik, Dmytro (Видавництво Львівської політехніки, 2024)
В статті потреба подальшого розвитку держави безпосередньо пов'язаний з: рішенням питань щодо підвищення обороноздатності та інформаційної безпеки; розвитком інформаційно-інтелектуальних систем. Обґрунтовується необхідність забезпечити потрібний рівень повноти інформації, дотримання вимог її актуальності, досягнення та підтримки належного рівня цілісності, доступності та конфіденційності. В статті наголошено, що для цього будуються комплексні системи кодування та захисту інформації. Показується, що останнім часом для додаткового підвищення рівня безпеки інформаційних ресурсів використовуються методи прихованого вбудовування інформації. В даній сфері науково-прикладних досліджень окреслюється напрямок своєчасної доставки цілісної відеоінформації в захищеному режимі. Для захисту можуть використовуватись: мета-повідомлення, які утворюються на основі інтелектуального аналізу відеокадрів; окремі відеосегменти аерофотознімків, що містять найбільш значиму для прийняття рішень інформацію. В даній статті досліджуються клас методів стеганографічних перетворень, які пов’язані з вбудовуванням повідомлень до цифрових контейнерів, які утворюються потоком відео-сегментів (ВС). Однак існуючі стеганографічні системи будуються переважно на використання кількості доступної до скорочення психовізуальної (ПСВ) надмірності. Тому збільшення стеганографічної ємності призводить до втрат цілісності та оперативності доставки відео-контейнерної інформації. Створено стеганокомпресійне кодування в стегано-поліадичному базисі на основі врахування допустимої для скорочення кількості надмірності. В цьому випадку в процесі компресії складових ВС організується безпосередня вбудовування прихованої інформації. Приховування інформації здійснюється технологічними етапами в залежності від компресійного перетворення перехідного синтаксису стегано-послідовність. Ключовим етапом є технологія двокаскадної імплементації доданих до стегано-послідовностей елементів приховується повідомлення до синтаксису стеганокомпресійного представлення складових ВС.

In the article, the need for further development of the state is directly related to: solving issues of increasing defense capability and information security; development of information and intelligent systems. The necessity of ensuring the required level of completeness of information, compliance with the requirements of its relevance, achievement and maintenance of the appropriate level of integrity, accessibility and confidentiality is substantiated. The article emphasizes that for this purpose, complex systems of coding and information protection are being built. It is shown that recently, in order to further increase the level of security of information resources, methods of hidden embedding of information have been used. In this field of scientific and applied research, the direction of timely delivery of integral video information in a secure mode is outlined. For protection, the following can be used: meta-messages, which are formed on the basis of intelligent analysis of video frames; separate video segments of aerial photographs containing the most important information for decision-making. This article examines a class of methods of steganographic transformations, which are associated with embedding messages in digital containers, which are formed by a stream of video segments (VS). However, existing steganographic systems are based mainly on the use of the amount of psychovisual (PSV) redundancy available for reduction. Therefore, an increase in steganographic capacity leads to a loss of integrity and efficiency of delivery of video-container information. Steganocompression coding in the stegano-polyadic basis was created on the basis of taking into account the amount of redundancy permissible for reduction. In this case, in the process of compression of the components of the VS, the direct embedding of hidden information is organized. Concealment of information is carried out by technological stages, depending on the compression transformation of the transitional syntax of the quilted sequence. The key stage is the technology of two-stage implementation of the elements of the concealed message added to the stegano sequences to the syntax of the steganocompression representation of the BC components.
Method of two-stage implantation of hidden information based on steganocompression transformations
Keywords: кодування інформації; відеозображення; стиснення; приховування інформації; стеганографія; відео контейнери; поліадичний базис; information encoding; video imaging; compression; information concealment; steganography; video containers; polyadic basis; 621.126